2019
DOI: 10.3390/ma12193226
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Isothermal Oxidation of Ir–Rh Spark Plug Electrodes

Abstract: High-temperature oxidation tests were performed on pure iridium, rhodium, and the iridium alloys, IrRh10, IrRh25, and IrRh40, at 1100 °C in a stable air environment for 60 h. The results of the oxidation were analyzed by X-ray photoelectron spectroscopy (XPS). Microstructural changes of the Ir–Rh alloys were characterized by scanning electron microscopy (SEM). XPS analysis results show that the main oxide of the Ir–Rh alloy in a 1100 °C environment was Rh2O3, and SEM analysis shows that the surfaces of the Ir–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Notably, the materials contain Ir species with two different valences, namely, metallic Ir (Ir 0 ) and oxidized Ir (Ir 4+ ). It suggests that some Ir particles were oxidized to hypervalent oxides (IrO x ) or bonded to hydroxyl groups (Ir(OH) x ), and the production of these components may alter the catalytic process of the materials . By calculating the relative intensity area of Ir 0 and Ir 4+ orbital peaks, the content proportions of high-valence Ir in the two materials were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the materials contain Ir species with two different valences, namely, metallic Ir (Ir 0 ) and oxidized Ir (Ir 4+ ). It suggests that some Ir particles were oxidized to hypervalent oxides (IrO x ) or bonded to hydroxyl groups (Ir(OH) x ), and the production of these components may alter the catalytic process of the materials . By calculating the relative intensity area of Ir 0 and Ir 4+ orbital peaks, the content proportions of high-valence Ir in the two materials were compared.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, rhodium oxide (RhOx) has been widely applied as an electrocatalyst due to its high stability and electrocatalytic activity for oxygen evolution. Alibek prepared Ti/IrO 2 –RhOx-ZrO 2 electrodes with different proportions of RhOx and found that increasing the content of RhOx led to improved service lifetime of the electrode. Swette reported that RhO 2 -coated electrodes with an oxide load of 10 g m –2 are highly stable against oxygen evolution in acidic electrolytes.…”
Section: Introductionmentioning
confidence: 99%